The Role of Instructional Leadership in Improving the Performance of Primary School Teachers Without Relevant Educational Background in the Subjects They Teach - Elma Yohana Purba; Lusiana Idawati (Publikasi Indonesia, 2025)
This research explores the role of instructional leadership in improving the performance of elementary school teachers who teach outside their educational background. A case study was conducted at SD ABC Bandar Lampung with subjects including the principal and three teachers who teach outside their field of expertise. The research used qualitative methods with an exploratory case study approach. Data was collected through in-depth interviews and classroom observations, then analyzed descriptively with source triangulation. The results showed that factors affecting teacher performance include intrinsic motivation, limited professional skills, administrative burden, and lack of curriculum flexibility. Effective instructional leadership strategies include providing scripted lesson plans, micro-teaching training, and clear vision-mission communication. However, the main challenges faced by principals are time constraints, lack of personal support, and poor communication with teachers. Although teachers demonstrate adequate performance, more proactive mentoring and continuous development programs are needed to improve teaching effectiveness